Self‐medication with alcohol or drugs for mood and anxiety disorders: A narrative review of the epidemiological literature - Turner, Sarah; Mota, Natalie; Bolton, James; Sareen, Jitender (Depression and anxiety, 2018)
Background The comorbidity of mood and anxiety disorders (MD and AD) with substance use disorders (SUD) is common. One explanation for this comorbidity is the self‐medication hypothesis, which posits that individuals with MD or AD use substances to cope with the difficult symptoms associated with the disorder. Over time, self‐medication (SM) can develop into an independent SUD. This narrative review will present the prevalence and correlates of SM with alcohol and/or drugs for MD and AD and the relationship between SM and subsequent SUD using both cross‐sectional and longitudinal epidemiological data. Methods Scopus and PsycINFO were searched from January 1997 to April 2018 to identify original research articles that examined the prevalence and correlates of SM and the temporal relationship between MD/AD and SUD in the general population (n = 22). Results The prevalence of SM with alcohol and/or drugs among those with MD or AD ranged from 21.9% to 24.1%. Male sex, younger age, being separated, divorced or widowed, and being Caucasian were characteristics associated with higher proportions of respondents endorsing SM with alcohol/drugs for MD and AD. Longitudinal data supports the temporal onset of primary MD/AD and secondary SUD among those who self‐report SM. Conclusion Providing and promoting alternate coping strategies for those with MD/AD may reduce SM, the development of SUD, and the comorbidity of MD/AD with SUD. The concurrent treatment of MD/AD and substance use is the current “gold standard” model of care, and the results of this review support its use.